Digital gait biomarkers in Parkinson’s disease: susceptibility/risk, progression, response to exercise, and prognosis - Martina Mancini; Mitra Afshari; Quincy Almeida; Sommer Amundsen-Huffmaster; Katherine Balfany; Richard Camicioli; Cory Christiansen; Marian L. Dale; Leland E. Dibble; Gammon M. Earhart; Terry D. Ellis; Garett J. Griffith; et al. (npj Parkinson's Disease)
Abstract This narrative review examines the utility of gait digital biomarkers in Parkinson’s disease (PD) research and clinical trials across four contexts: disease susceptibility/risk, disease progression, response to exercise, and fall prediction. The review of the literature to date suggests that upper body characteristics of gait (e.g., arm swing, trunk motion) may indicate susceptibility/risk of PD, while pace aspects (e.g., gait speed, stride length) are informative for tracking disease progression, exercise response, and fall likelihood. Dynamic stability aspects (e.g., trunk regularity, double-support time) worsen with disease progression but can improve with exercise. Gait variability emerges as a sensitive biomarker across all 4 contexts but with low specificity. The lack of standardized gait testing protocols and the lack of a minimum set of quantified digital gait biomarkers limit data harmonization across studies. Future studies, using a commonly agreed upon protocol, could be used to demonstrate the utility of specific gait biomarkers for clinical practice.